An Empirical Study of Financial Disclosures (Book). - Ramaglia, Judith; Moriarity, Shane R. (The Accounting Review, 1991)
Abstract Reviews the book "An Empirical Study of Financial Disclosures by Swedish Companies," by T. E. Cooke.